Sumbangan Teknologi Hijau Dalam Ketamadunan Islam (Sains Humanika, 2016)
Green technology refers to the development and application of products, equipment and systems to protect the environment and the natural environment and minimize the negative impact of human activities. Positive elements in green technologies should be focused on the elements that benefit the environment. But otherwise have occurred. Human activities have resulted in a variety of greedy negative changes to the earth such as climate change, global warming and pollution. This is because man has lost Islamic values in themselves. Therefore, how green technology can contribute to Islamic civilization and portrays Islam entirely discussed in this article. The objective of this study is to analyze how green technology can contribute to Islamic civilization and can filled with features that prescribed in Islam. This study will use qualitative methods in which sources of information from journal articles, books and online database. Findings have shown that the green technology can contribute in Islamic civilization and show that green technology has been filled with the value of Islam such as environmental protection, energy saving and environmental sustainability awareness. These areas have also contributed in terms of environmental protection and restore human civilization increasingly barren due to the greed in this world. Studies of green technology can also provide a space for Muslims to explore this area in accordance with the Quran and the Sunnah and thus can contribute to environmental sustainability, which result in benefits to the present generation and the next.
Keywords: Green technology; sustainable; islamic civilization